Late Pleistocene speciation of three closely related tree peonies endemic to the Qinling–Daba Mountains, a major glacial refugium in Central China. Issue 13 (17th June 2019) - Xu, Xing‐Xing; Cheng, Fang‐Yun; Peng, Li‐Ping; Sun, Yan‐Qiang; Hu, Xian‐Ge; Li, San‐Yuan; Xian, Hong‐Li; Jia, Kai‐Hua; Abbott, Richard J.; Mao, Jian‐Feng
Abstract: Determining the factors promoting speciation is a major task in ecological and evolutionary research and can be aided by phylogeographic analysis. The Qinling–Daba Mountains (QDM) located in central China form an important geographic barrier between southern subtropical and northern temperate regions, and exhibit complex topography, climatic, and ecological diversity. Surprisingly, few phylogeographic analyses and studies of plant speciation in this region have been conducted. To address this issue, we investigated the genetic divergence and evolutionary histories of three closely related tree peony species ( Paeonia qiui, P. jishanensis, and P. rockii ) endemic to the QDM. Forty populations of the three tree peony species were genotyped using 22 nuclear simple sequence repeat markers (nSSRs) and three chloroplast DNA sequences to assess genetic structure and phylogenetic relationships, supplemented by morphological characterization and ecological niche modeling (ENM). Morphological and molecular genetic analyses showed the three species to be clearly differentiated from each other. In addition, coalescent analyses using DIYABC conducted on nSSR variation indicated that the species diverged from each other in the late Pleistocene, while ecological niche modeling (ENM) suggested they occupied a larger area during the Last Glacial Maximum (LGM) than at present. The combined genetic evidence from nuclear and chloroplast DNA and the results of ENM indicate that each species persisted through the late Pleistocene in multiple refugia in the Qinling, Daba, and Taihang Mountains with divergence favored by restricted gene flow caused by geographic isolation, ecological divergence, and limited pollen and seed dispersal. Our study contributes to a growing understanding of the origin and population structure of tree peonies and provides insights into the high level of plant endemism present in the Qinling–Daba Mountains of Central China. Abstract : Here, we report an investigation of the evolutionary histories of three closely related tree peony species ( Paeonia qiui, P. jishanensis, and P. rockii ) endemic to the Qinling–Daba Mountain range, which is an important geographic barrier between the northern temperate and southern subtropical regions of mainland China. Our investigation is based on an analysis of twenty‐two nuclear simple sequence repeats (nSSRs) markers and three chloroplast DNA fragments. In addition, we examined morphological differences between these species and niche divergence using ecological niche modeling (ENM). Speciation across these mountain areas is expected to have been favored by restricted gene flow caused by geographic isolation and ecological divergence between refugia, and low pollen and seed dispersal. Unlike many other species which shifted their distributions in response to climate changes.